JENIS-JENIS DAN POTENSI JAMUR MAKROSKOPIS YANG TERDAPAT DI PT PERKEBUNAN HASIL MUSI LESTARI DAN PT DJUANDA SAWIT KABUPATEN MUSI RAWAS - Linna Fitriani; Yuni Krisnawati; Msy Olivia Rega Anorda; Ketri Lanjarini (LP4MK STKIP PGRI Lubuklinggau, 2018)
This study aimed to determine the types and potential of macroscopic fungi in oil palm plantations at PT Musi Lestari Plantation and PT Djuanda Sawit Plantation in Musi Rawas Regency. This research is descriptive qualitative research. Sampling is done by using a purposive sampling method with roaming techniques. The macroscopic fungal species found in the field were made into wet herbarium and identified. The research data were analyzed descriptively. The results of the study obtained 35 species. 35 species of macroscopic fungi including Clitoybe dealbata, Clitoybe decembris, Collybia sp., Collybia chirata, Collybia confluens, Collybia butyracea, Marasminus sp., Boletus sp., Hipholoma marginatum, Pleurotus varreatus, Pleurotus ostreatus, Crepurususus spidus, Crepurususus sp. rameus, Lactarius sp., Volvariella volvaceae, rhacodes Lepiota, Amanita fulva, Amanita virosa, Parasola lactea, Auricularia polytricha, Spongipelis sp., Grivola sp., Grivola sp., Grivola sp., Fvom phomentarius, Ganoderma sp. , Panus sp., Coltricia sp., Coltricia perennes, Pycnoporus cinnabarinus, Tulostoma sp., Lycoperdon gemmatum, Peziza repanda, and Peziza vesiculosa. The conclusions of 35 species were found, belonging to 6 orders, 16 families, and 24 genera. 8 species or 23% macroscopic fungi can be consumed.